Group III – Nitride Semiconductors: Preeminent Materials for Modern Electronic and Optoelectronic Applications - Acharya, Ananta R. (Himalayan Physics, 2015)
Over the past two decades, group III-nitride semiconductors have become the focus of extremely intensive research due to their unique physical properties and their high potential for use in numerous electronic and optoelectronic devices. To date, almost all aspects of these materials have been explored, from understanding the fundamental physical properties to the development of fabrication technology of highly efficient devices for commercial use. In this article, some of the important physical properties and applications of III-nitride semiconducting materials have been presented. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 22-26